'We teach them to be university students’ The role of peer educators in the provision of ontological access to higher education - Winberg, Chris (Critical Studies in Teaching and Learning, 2023)
This special issue draws together five papers presented at the Higher Education Close-Up 9 conference, held in Cape Town in November 2018. The theme of the conference was 'Higher Education in Contemporary Times, and papers covered a wide range of issues facing higher education in these complex times in which we now live, marked by political and social change, climate change, rapid technological advancement, and an ever-uncertain future. The 5 papers in this issue focus specifically on issues related to teaching, the scope of the Journal, looking at tutoring and ontological access, MOOCs and opening up knowledge to more diverse audiences, mathematics learning and students' self-belief, the future of universities of technology, and working with students from rural backgrounds making challenging transitions to higher education.